IMPROVING STUDENTS READING COMPREHENSION IN NARRATIVE TEXT BY USING PICTURE STORY - Paputungan, Vira Triana; Kamagi, Sarah; Rorimpandey, Rinny (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2022)
The aim of this study is to find out whether the use of picture story is effective to improve students reading comprehension especially using the stories of narrative text The stories presented are themed local stories in the country Cerita Rakyat< em> because students are still not familiar with the story In this study the writers adjust to the level of students thinking Therefore picture story is one of the considerations where this media is able and effective to improve students reading comprehension The approach of this study is quantitative Multiple Choice and True or False test are used as the instruments eliciting the data The subject of this study was the seventh grade students of SMP Negeri 5 Bolaang The result shows that there is an increase between the pre test 11 85 and the post test 14 75 This indicates that picture story improve students reading comprehension This is suggested that picture story can be used as effective media in improve students reading comprehension < p>